2018
DOI: 10.1590/rbz4720160390
|View full text |Cite
|
Sign up to set email alerts
|

HSF1 and HSPA6 as functional candidate genes associated with heat tolerance in Angus cattle

Abstract: The purpose of this study was to access and characterize single nucleotide polymorphisms (SNP) located within the HSF1 and HSPA6 candidate genes for adaptability in Angus breed raised in subtropical climate. Samples of DNA from 20 animals representing extreme phenotypes for adaptability traits were obtained. Sequence variations in the candidate genes were described by sequencing target regions. We identified 12 SNP located in the HSF1 gene. Moreover, four of the six SNP found in the HSPA6 gene cause amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Respiration rate and body core temperature have been recommended as suitable parameters to assess individual heat loads of dairy cows at an early stage, whereas feeding behaviour may depend on the physiological stage of the cow [66]. In mammals, exposure to hypothermia or hyperthermia has been related to morphological and physiological alterations [67]. In the present study, we observed that almost all the cows sought shade as the heat intensity increased, indicating obvious distress and a search for shelter from the direct sun.…”
Section: Discussionmentioning
confidence: 99%
“…Respiration rate and body core temperature have been recommended as suitable parameters to assess individual heat loads of dairy cows at an early stage, whereas feeding behaviour may depend on the physiological stage of the cow [66]. In mammals, exposure to hypothermia or hyperthermia has been related to morphological and physiological alterations [67]. In the present study, we observed that almost all the cows sought shade as the heat intensity increased, indicating obvious distress and a search for shelter from the direct sun.…”
Section: Discussionmentioning
confidence: 99%
“…This study predicted a putative novel HSPE1 transcript with alternative 5′ splice site more expressed in HIF animals. SNPs (Single nucleotide polymorphisms) found in HSP family genes were associated with thermal tolerance traits in Chinese Holstein 56 and Angus cattle 57 . Heat shock proteins provide subsidies for cells to identify and promote the refolding of damaged proteins or target them to appropriate proteolytic systems, thereby helping to eliminate proteins whose damage is not suitable for recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Besides heat stress (Baena et al, 2018; Sales et al, 2018), heat shock proteins (HSP) are being evaluated in apoptosis, oxidative stress, inflammatory diseases, cancer (Ikwegbue et al, 2017), virus infection (Shan et al, 2018), bacterial infection (Kim et al, 2018), as immunomodulators (Edkins et al, 2017; Zininga et al, 2018), therapeutics (Skórzynska-Dziduszko et al, 2018), and diagnostics (Lechner et al, 2018; Tang T. et al, 2018). HSPs have diagnostic role in ischemic injury of cardiomyocytes (Santos et al, 2018), inflammatory process of multiple sclerosis (Lechner et al, 2018), early diagnosis of lung cancer (Tang T. et al, 2018), proteome stress (Liu and Zhang, 2018), bipolar disorder (Cheng et al, 2018), and anti-apoptotic agent (Jang et al, 2018).…”
Section: Heat Shock Proteins (Hsps)mentioning
confidence: 99%